Understanding Medical Education - Oscar Gilang Purnajati (Berkala Ilmiah Kedokteran Duta Wacana, 2023)
The content of this book is comprehensive and complete in only one book which allows the reader to understand step-by-step medical education, or simply to look for a certain point of information because in this book each section is divided into chapters and is supported by appendix pages which make it easier to find the study material. Readers' understanding is easier to obtain with this book because the English used is easy to understand, but the small font size may be quite tiring for some readers. Reviewers recommend this book as a reliable and easy-to-understand reference, especially for preclinical and clinical medical educators.